Electrical properties of doped conjugated polyelectrolytes with modulated density of the ionic functionalities. Issue 99 (20th October 2015) - Mai, Cheng-Kang; Arai, Tomoya; Liu, Xiaofeng; Fronk, Stephanie L.; Su, Gregory M.; Segalman, Rachel A.; Chabinyc, Michael L.; Bazan, Guillermo C.
Abstract : We report the synthesis of a series of water soluble anionic narrow band-gap conjugated polyelectrolytes with a varied density of the ionic functional groups. Abstract : We report the synthesis of a series of water-soluble anionic narrow band-gap conjugated polyelectrolytes with a varied density of the ionic functional groups. The charge density is modulated by incorporating the structural units with tetraethylene glycol (TEG) monomethyl ether side chains. These polymers are readily p-doped during dialysis in water. CPEs with TEG side chains exhibit tighter intermolecular packing in the solid state and higher electrical conductivity.